Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1097/01.pec.0000202454.19237.b0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rapid Influenza Testing at Triage on Management of Febrile Infants and Young Children

Abstract: A triage protocol for rapid influenza testing for febrile infants and children appears to significantly decrease additional testing, time in the ED, and charges in children testing positive for influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 26 publications
1
64
2
4
Order By: Relevance
“…While carefully considering the possibility of false-positive testing, rapid antigen testing of young febrile infants during influenza season may also assist with medical decision making. Definitive diagnosis also leads to decreased testing, decreased antibiotic use, and shorter stays in the emergency department, all of which help to decrease medical costs (1,6,7). This study compared the detection of influenza virus from secretions from the AN in a rapid antigen test when specimens were collected with polyurethane foam swabs to detection when specimens were collected with flocked nylon swabs.…”
Section: Rapid Antigen Detection For Influenza Virus Infection Continmentioning
confidence: 99%
See 1 more Smart Citation
“…While carefully considering the possibility of false-positive testing, rapid antigen testing of young febrile infants during influenza season may also assist with medical decision making. Definitive diagnosis also leads to decreased testing, decreased antibiotic use, and shorter stays in the emergency department, all of which help to decrease medical costs (1,6,7). This study compared the detection of influenza virus from secretions from the AN in a rapid antigen test when specimens were collected with polyurethane foam swabs to detection when specimens were collected with flocked nylon swabs.…”
Section: Rapid Antigen Detection For Influenza Virus Infection Continmentioning
confidence: 99%
“…Rapid diagnosis also aids clinical management by differentiating influenza from other viral illnesses and allows the option of timely antiviral therapy for maximum effectiveness (20,25). Previous research has also shown that a diagnosis of influenza not only decreases antibiotic use but also decreases testing and the length of stay in the ED (1,6,7).…”
mentioning
confidence: 99%
“…25.2%) 5,22) . 신속 항원검사로 인플루엔자를 조기에 진단한 경우, 검사 및 치료 등에 따른 비용이 적었고 23) , 뇌척수액 장바이러스 양성 군에서 그렇지 않은 군보다 입원일수가 하는데 주의를 요한다 8,15) . …”
Section: 바이러스 검사와 세균 검사unclassified
“…However, some pediatric-specific pathways have been shown to have an effect on ED patient flow. [73][74][75] Developing emergency care pathways that adequately address pediatric issues and prioritize problems in accordance with those of adults is a priority. An increasing number and quality of pediatric-specific triage pathways are available, the most notable being the 5-level triage system.…”
Section: Emergency Care Pathwaysmentioning
confidence: 99%